Cyclical skill-biased technological change - Almut Balleer; Thijs van Rens (Institute for the Study of Labor (IZA), 2009)
Over the past two decades, technological progress has been biased towards making skilled labor more productive. What does skill-biased technological change imply for business cycles? To answer this question, we construct a quarterly series for the skill premium from the CPS and use it to identify skill-biased technology shocks in a VAR with long run restrictions. We find that hours worked fall in response to skill-biased, but not in response to skill-neutral improvements in technology. Skill-biased technology shocks are associated with increases in the relative price of investment, indicating that capital and skill are substitutes in aggregate production.
urn:nbn:de:101:1-20090720265
Keywords: E24; E32; J24; J31; 330; Skill-biased technology; skill premium; VAR; long-run restrictions; capital-skill complementarity; business cycle; Qualifikation; Technischer Fortschritt; Hochqualifizierte Arbeitskräfte; Bildungsertrag; Schock; Konjunktur; Produktionsfaktor; Komplementärgut; USA